Late-medieval prison writing and the politics of autobiography - Summers, Joanna (Oxford English monographs., 2004)
Boethius's 'Consolation of philosophy' has long been taken as one of the seminal works of the Middle Ages, yet despite study of many aspects of this book, the legacy of the figure of the writer in prison has not been explored. This title explores autobiographical identity in a group of late medieval 'prison texts'.